Pemetaan Lahan Parkir dengan Metode Polygon untuk Pendapatan Asli Daerah Kota Pekalongan - Tri Agus Setiawan; Agus Ilyas; Sattriedi Wahyu Binabar (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2021)
Parking is a potential regional revenue which is quite high because it is realized that the number from year to year has increased. Based on data from the Pekalongan City Transportation Service, in 2019 it has reached Rp. 1,205 billion or 75 percent of the target set, which is Rp. 1.6 billion. The parking area managed by the Pekalongan City Government so far has managed 424 points, the types of fees managed are divided into parking fees on the edge of public roads and off-street parking with a composition of 30 percent of PAD and 70 percent for parking attendants. The existence of this considerable potential poses a challenge for local governments to manage it. In the implementation of roadside retribution policies, there have been problems in managing parking lots, including the existence of strategic parking areas but not registered with the local government, the distribution and area of ??managed parking lots so that potential parking levy tax revenues can be known. In the research conducted using quantitative, qualitative, and R&D research methods with mapping with the polygon method so that the parking area managed by the Pekalongan City Government and the potential income from parking retribution taxes as a Pekalongan City Original Revenue Source (PAD) can be found.. Keywords: GIS, polygon, retribution, PAD